Do populists want direct democracy? Examining how thick and thin populist attitudes are associated with the Finnish Citizens’ Initiative - Christensen Henrik Serup; Setälä Maija (Taylor & Francis, 2025)
Theoretical works suggest that populist attitudes are associated with demands for direct democracy in the form of referendums. However, it remains unclear how populist attitudes relate to other direct-democratic instruments such as citizens’ initiatives. We therefore examine whether populist attitudes affect the attitudes toward the Citizens’ Agenda Initiative (CI) in Finland with the help of the national election study from 2019 (n = 1598). We study (1) whether populist attitudes are associated with positive attitudes towards the CI (2) whether populist attitudes increase the use of the CI, and (3) the interplay between anti-elitism, anti-immigration, and anti-pluralism as driving forces behind attitudes towards and using the CI. The results suggest that anti-elitism has a negative link to satisfaction with the CI, and anti-pluralism is associated with lower likelihood of using the CI. Hence there is little to suggest that populist attitudes are strong drivers of involvement in this kind of direct-democratic participation.